EFEK KLINIS APLIKASI SUBGINGIVAL RACIKAN GEL METRONIDASOL 25% DAN LARUTAN POVIDON-IODIN 10% SEBAGAI TERAPI PENUNJANG SKELING-PENGHALUSAN AKAR PADA PERIODONTITIS KRONIS - Trijani Suwandi (Faculty of Dentistry, Universitas Indonesia, 2015)
Metronidazole gel 25% as an adjunct to scaling and root planing showed clinical effect better than scaling and root-planing alone. In Indonesia metronidazole gel is not popular, since probably it is expensive and not easy to obtain. So there is an idea to make metronidazole gel 25% mixture with relatively cheaper. The purpose of the study was to evaluate clinical effect of metronidazole gel 25%. Thirty Chronic Adult Periodontitis patients possessing at least 3 teeth ≥6mm pocket depth, ≥4mm attachment loss, and bleeding on probing were selected and grouped into metronidazole 25%, PVP-I 10%, and as controle respective. After SRP of all quadrant, 3 teeth were randomly selected as respectively metronidazole gel 25% and PVP-I 10% were applied on day 0 and day 7. BOP, PPD, and clinical attachment gain were recorded at baseline and 1 month post therapy. Bleeding on probing was analyzed using Kruskal-Wallis test, pocket depth and attachment gain were analyzed using Anova test. The result showed a significant difference in each group before and after the application. However, metronidazole group was the best compared to the other two groups.